Molecular epidemiology of continued Plasmodium falciparum disease transmission after an outbreak in Ecuador - Ruybal-Pesántez, Shazia; Sáenz, Fabián E.; Deed, Samantha L.; Johnson, Erik K.; Larremore, Daniel B.; Vera-Arias, Claudia A.; Tiedje, Kathryn E.; Day, Karen P. (Frontiers in Tropical Diseases, 2023)
To better understand the factors underlying the continued incidence of clinical episodes of falciparum malaria in E-2025 countries targeting elimination, we characterized the molecular epidemiology of Plasmodium falciparum disease transmission after a clonal outbreak in Ecuador. Here we study disease transmission by documenting the diversity and population structure of the major variant surface antigen of the blood stages of P. falciparum encoded by the var multigene family. We used a high-resolution genotyping method, “varcoding”, involving targeted amplicon sequencing to fingerprint the DBLα encoding region of var genes to describe both antigenic var diversity and var repertoire similarity or relatedness in parasite isolates from clinical cases. We identified nine genetic varcodes in 58 P. falciparum isolates causing clinical disease in 2013-2015. Network analyses revealed that four of the varcodes were highly related to the outbreak varcode, with identification of possible diversification of the outbreak parasites by recombination as seen in three of those varcodes. The majority of clinical cases in Ecuador were associated with parasites with highly related or recombinant varcodes to the outbreak clone and due to local transmission rather than recent importation of parasites from other endemic countries. Sharing of types in Ecuadorian varcodes to those sampled in South American varcodes reflects historical parasite importation of some varcodes, especially from Colombia and Peru. Our findings highlight the translational application of varcoding for outbreak surveillance in epidemic/unstable malaria transmission, such as in E-2025 countries, and point to the need for surveillance of local reservoirs of infection in Ecuador to achieve the malaria elimination goal by 2025.